Testing Telepathy in the Medium/Proxy-Sitter Dyad: A Protocol Focusing on the Source-of-Psi Problem - Rock, Adam; Storm, Lance (Journal of Scientific Exploration, 2015)
<!–[if gte mso 9]> 0 0 1 154 879 UNE 7 2 1031 14.0 96 <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-AU JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Cambria; –> <!–[endif] –> <!–StartFragment–>Numerous mediumship studies (e.g., Beischel & Schwartz, 2007; Kelly & Arcangel, 2011; Rock, Beischel, Boccuzzi, & Bisuso, 2014) have reported statistically significant results and, thus, suggest that various contemporary mediums are able to demonstrate anomalous information reception (AIR) under laboratory conditions. Importantly, however, such studies are unable to address the source of mediums’ AIR. Indeed, the source-of-psi problem (survival-psi and living agent psi being the most likely contenders) cannot be resolved using current methodologies (Beischel, 2012). However, innovative mediumship-testing techniques may produce results that indicate a convergence towards one alternative or another (Jamieson & Rock, 2014). We present the methodology of one such test focused on investigating whether mediums, who work with well-rehearsed but ‘blind’ proxy-sitters, create telepathic links that we refer to as dyad-telepathy, thereby producing response sets that indicate the psi source is unlikely to be a discarnate entity.<!–EndFragment–>